Molecular records of climate variability and vegetation response since the Late Pleistocene in the Lake Victoria basin, East Africa - Berke, M.; Johnson, T.; Werne, Josef; Grice, Kliti; Schouten, S.; Damste, J. (Pergamon, 2012)
New molecular proxies of temperature and hydrology are helping to constrain tropical climate change and elucidate possible forcing mechanisms during the Holocene. Here, we examine a ∼14,000 year record of climate variability from Lake Victoria, East Africa, the world's second largest freshwater lake by surface area. We determined variations in local hydroclimate using compound specific δD of terrestrial leaf waxes, and compared these results to a new record of temperature utilizing the TEX86 paleotemperature proxy, based on aquatic Thaumarchaeotal membrane lipids. In order to assess the impact of changing climate on the terrestrial environment, we generated a record of compound specific δ13C from terrestrial leaf waxes, a proxy for ecosystem-level C3/C4 plant abundances, and compared the results to previously published pollen-inferred regional vegetation shifts. We observe a general coherence between temperature and rainfall, with a warm, wet interval peaking ~10–9 ka and subsequent gradual cooling and drying over the remainder of the Holocene. These results, particularly those of rainfall, are in general agreement with other tropical African climate records, indicating a somewhat consistent view of climate over a wide region of tropical East Africa. The δ13C record from Lake Victoria leaf waxes does not appear to reflect changes in regional climate or vegetation. However, palynological analyses document an abrupt shift from a Poaceae (grasses)-dominated ecosystem during the cooler, arid late Pleistocene to a Moraceae-dominated (trees/shrubs) landscape during the warm, wet early Holocene. We theorize that these proxies are reflecting vegetation in different locations around Lake Victoria.Our results suggest a predominantly insolation-forced climate, with warm, wet conditions peaking at the maximum interhemispheric seasonal insolation contrast, likely intensifying monsoonal precipitation, while maximum aridity coincides with the rainy season insolation and the interhemispheric contrast gradient minima. We interpret a shift in conditions at the Younger Dryas to indicate a limited switch in insolation-dominated control on climate of the Lake Victoria region, to remote teleconnections with the coupled Atlantic and Pacific climate system.